MOF derived mesoporous K-ZrO2 with enhanced basic catalytic performance for Knoevenagel condensations - Wang, P.; Feng, J.; Zhao, Y.; Gu, S.; Liu, Jian (Royal Society of Chemistry, 2017)
© 2017 The Royal Society of Chemistry. Mesoporous K-ZrO 2 are designed and synthesized through a direct heat-treatment process of a KNO 3 loaded UiO-66 metal organic framework. Very interestingly, the carbon intermediates formed during the heat-treatment process can act both as mesoporous templates and base-resistant reinforcement for zirconia. The resultant mesoporous K-ZrO 2 catalysts with high surface area show excellent catalytic performance in Knoevenagel condensations, especially for substrates with large molecular size. The mesoporous KZ also show enhanced activity when compared to KZ synthesized from traditional zirconium hydroxides. To the best of our knowledge, this is the first synthesis of a metal-oxide type solid base with a MOF precursor.